2012
DOI: 10.1111/j.1540-8175.2012.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Function Predicts Clinical Response to Specific Vasodilator Therapy in Patients with Pulmonary Hypertension

Abstract: Over an average period of 1 year, almost half of patients showed signs of clinical deterioration despite specific vasodilator therapy. Parameters of right ventricular morphology and function had prognostic value in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 47 publications
1
27
0
7
Order By: Relevance
“…It has been speculated that changes in pulmonary vascular impedance resulting from vascular stiffening might have the potential to be a better predictor of prognosis and outcome than pulmonary vascular resistance . Reduced pulmonary vascular distensibility may importantly increase the pulsatile component of the hydraulic load of the right ventricle with detrimental effects on the right ventricular‐pulmonary circulation unit, but, although the importance of RV function impairment has been recognized and intensively studied in PH, standardized echocardiographic parameters for the assessment of pulmonary vascular stiffness still need to be established . Pulmonary pulse transit time as a potential index of pulmonary vascular stiffness might thus be a promising parameter in the future evaluation of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that changes in pulmonary vascular impedance resulting from vascular stiffening might have the potential to be a better predictor of prognosis and outcome than pulmonary vascular resistance . Reduced pulmonary vascular distensibility may importantly increase the pulsatile component of the hydraulic load of the right ventricle with detrimental effects on the right ventricular‐pulmonary circulation unit, but, although the importance of RV function impairment has been recognized and intensively studied in PH, standardized echocardiographic parameters for the assessment of pulmonary vascular stiffness still need to be established . Pulmonary pulse transit time as a potential index of pulmonary vascular stiffness might thus be a promising parameter in the future evaluation of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found to be significantly associated with hemodynamic as well as other two‐dimensional (2D) echocardiographic parameters of RV function . In addition, recent studies have shown that RV longitudinal strain may be a useful prognostic marker in patients with pulmonary arterial hypertension (PAH) …”
mentioning
confidence: 99%
“…The association of ventricular dysfunction and mortality in patients with Eisenmenger syndrome is consistent with other research which has found ventricular function to be a strong predictor of adverse outcomes in many forms of congenital heart disease, 7,8 including Eisenmenger's syndrome. 9,10 In the current study, biventricular dysfunction conveyed an even higher risk with a survival probability of <40% at 5 years. Unlike previous reports in Eisenmenger syndrome, this study was prospective with protocolled quantitative analysis of ventricular function, which strengthens the authors' conclusions.…”
Section: See Article By Jensen Et Almentioning
confidence: 50%